2021
DOI: 10.5222/terh.2021.73626
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Chemotherapy on the EORTC QLQ-C30 and LC-13 Quality of Life Scales in Patients with Lung Cancer

Abstract: Objective: The concept of quality of life (QoL) in lung cancer includes many physical, psychological and social components. We aimed to assess the effect of chemotherapy (CT) on QoL of lung cancer patients using QoL scales. Methods: Fifty inoperable lung cancer patients who were newly diagnosed and taken into a CT plan were included. Patients were followed in terms of responsiveness and toxicity. Turkish versions of the EORTC QLQ-C30 and LC13 scales were used before every cycles. Results: The average age was 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(29 reference statements)
1
0
0
Order By: Relevance
“…In current study, the highest percentage of samples were illiterate and had a significant association with quality of life this agrees with the study shows that education is one factor that positively affects QoL. Moreover, patients who completed primary or further education were observed to have better social and physical functions [16,17]. In this study, most of the participants were living in rural areas, which was supported by a study that reported lung cancer more frequently caused death in rural areas [18].…”
Section: Methodssupporting
confidence: 89%
“…In current study, the highest percentage of samples were illiterate and had a significant association with quality of life this agrees with the study shows that education is one factor that positively affects QoL. Moreover, patients who completed primary or further education were observed to have better social and physical functions [16,17]. In this study, most of the participants were living in rural areas, which was supported by a study that reported lung cancer more frequently caused death in rural areas [18].…”
Section: Methodssupporting
confidence: 89%